Vascular dementia : risk factors, diagnosis, and treatment - Jacobsen, Sarah R. (Neuroscience Research Progress., 2011)
"Vascular dementia is the second most common form of dementia after Alzheimer's disease in older adults. The term refers to a group of syndromes caused by different mechanisms all resulting in vascular lesions in the brain. Early detection and accurate diagnosis are important, as vascular dementia is at least partially preventable. Risk factors for vascular dementia include hypertension, smoking, hypercholesterolemia, diabetes mellitus, and cardiovascular and cerebrovascular disease. This book presents current research from across the globe in the study of vascular dementia, including GRK2 over-expression in the context of early Alzheimer disease pathogenesis; vitamin deficiencies and vascular dementia; biofluid markers as potential markers for vascular dementia; and the epidemiology of vascular dementia."--Google Books viewed Mar. 23, 2021.